Surgical management of nonbacterial thrombotic endocarditis in malignancy - Daisuke Kaneyuki; Kaoru Matsuura; Hideki Ueda; Hiroki Kohno; Michiyo Kanbe; Goro Matsumiya (Surgical Case Reports, 2017)
Abstract Background Nonbacterial thrombotic endocarditis is commonly seen on heart valves in patients with malignant or collagen diseases. The natural prognosis of nonbacterial thrombotic endocarditis is reported to be poor due to underlying malignancy. Surgical indications and appropriate timing for surgery for nonbacterial thrombotic endocarditis and underlying malignancy have not been formally studied. Case presentation The case was a 45-year-old woman who presented with a history of systemic embolization associated with occult malignancy. A preoperative transesophageal echocardiogram showed multiple mobile vegetations on the aortic and mitral valves. She underwent valve surgery to prevent recurrent embolization. Based on the histopathologic findings, she was diagnosed with nonbacterial thrombotic endocarditis. She subsequently underwent surgery for occult malignancy, which was diagnosed as endometrioid adenocarcinoma. Conclusions Although surgical indications for nonbacterial thrombotic endocarditis remain unclear, valve replacement or repair and multidisciplinary treatment including surgical intervention are essential to prevent recurrent embolization in patients with nonbacterial thrombotic endocarditis associated with malignancy.